1998
DOI: 10.1039/a707269d
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic study of the binding of hexathia-18-crown-6-tetraone with some transition and heavy metal ions in dimethyl sulfoxide solution

Abstract: A conductance study of the interaction between CO2`, Ni2`, Cu2`, Zn2`, Cd2`, Pb2`and Hg2`ions with hexathia-18-crown-6-tetraone in dimethyl sulfoxide solution has been carried out at various temperatures. Formation constants of the resulting 1 : 1 complexes were determined from the molar conductanceÈmole ratio data and found to vary in the order Hg2` [ Pb2`[ Cd2`[ Cu2`[ Ni2`[ Co2`[ Zn2`. The enthalpy and entropy of complexation were determined from the temperature dependence of the formation constants. All com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(33 citation statements)
references
References 37 publications
0
33
0
Order By: Relevance
“…The results showed that, in all cases, the ligand to cation mole ratio was 1. The formation constants (K f ) of the resulting 1 : 1 complexes were evaluated by the computer fitting of the molar conductance-mole ratio data to appropriate equations [20,21].The stability of the resulting complexes were varied in the order of:…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that, in all cases, the ligand to cation mole ratio was 1. The formation constants (K f ) of the resulting 1 : 1 complexes were evaluated by the computer fitting of the molar conductance-mole ratio data to appropriate equations [20,21].The stability of the resulting complexes were varied in the order of:…”
Section: Resultsmentioning
confidence: 99%
“…Thus, in preliminary experiments, the complexation of SBTD with a number of alkali, alkaline earth, transition and heavy metal ions was studied conductometrically in acetonitrile solution at 25±0.05 °C 24,25 , in order to obtain information about the stability and selectivity of the resulting complexes. The complex formation constant, K f , of the resulting 1:1 complexes were evaluated by computer fitting of the molar conductance-mole ratio data to appropriate equations 24,25 , and the results are summarized in Table 1. As can be seen, the SBTD could act as a suitable complexing agent for pre-concentration and separation of copper ions via solid extraction, by using octadecyl bonded silica membrane disks.…”
Section: Resultsmentioning
confidence: 99%
“…The break-through volume of sample solution by dissolving 2 µg of copper in 25,50,100,250,500,750,1000,1250,1500,1750,2000,2250,2500, 3000 and 3500 mL of water, was tested and the recommended procedure was followed and the results showed that the extraction by modified membrane disk was found to be quantitative, up to 2500 mL. Thus, the break-through volume for the method is more than 2500 mL.…”
Section: Determination Of Break-through Volumementioning
confidence: 99%
“…[27][28][29][30][31] The complex formation constant, K f , shows the selectivity of the used ionophore toward Ho 3+ ions (K f 5.7×10 6 ) among the all other cations tested.…”
Section: Potential Response Of Tpa-pvc Membrane Sensormentioning
confidence: 99%